Finite element simulations of thermal residual stresses in realistic 3D WC-Co microstructures. (December 2019) - Öhman, Mikael; Ekh, Magnus; Larsson, Fredrik; Wahnström, Göran
Abstract: During cooling of WC-Co cemented carbides from sintering temperatures, large internal residual stresses are obtained due to the difference in thermal expansion of WC and Co. The residual stresses depend on the properties of the microstructure, such as volume fractions and morphology, as well as the thermomechanical properties of the constituents. These residual stresses affect the engineering performance and strength of the hardmetal. In this paper, we present finite element simulations of the cooling of realistic synthetic WC-Co microstructures from sintering temperatures to room temperature. The microstructures are generated in voxel grids using a newly developed tool CCBuilder. Finite element analyses are conducted to obtain effective macroscopic thermomechanical properties and thermal residual stresses of WC-Co microstructures in a free sintered specimen. The analyses are performed within the framework of multi-scale computational homogenization using periodic boundary conditions. In the analyses individual anisotropic elastic and thermal properties of WC-grains are accounted for. An excellent agreement between numerically predicted and experimental results for the macroscopic thermomechanical properties for WC-Co is obtained. In addition, the predicted residual stresses in the microstructure after cooling are in good agreement with experimental data. The influence from different constitutive model assumptions (elasticity, elastoplasticity) for the Co-phase on the residual stresses is studied. Finally, the proposed modelling framework is used to study the influence of WC-grain geometry on the residual stress field and our results show a substantial dependency of the residual stresses on the detailed morphology of the microstructure. In conclusion, we demonstrate the power of the presented modelling framework using realistic synthetic 3D microstructures with periodic boundary conditions together with multi-scale computational homogenization. In the future it may be open up strategies for optimal material design of microstructures of WC-Co cemented carbides. Highlights: Finite element modelling using realistic 3D WC-Co microstructures Computational homogenization for prediction of thermo-elastic properties Numerical predictions of residual stresses for free sintering Parameter studies of thermo-elastic properties of WC and mechanical behavior of Co Numerical studies of influence of WC-grain geometry